The Effect of SRP and Lunar Attraction on the Inclined MEO Satellite - Saleh, Abdulrahman; Ghanem, Hind (Iraqi Journal of Science, 2024)
In this paper some perturbations of a satellite orbit with heights more than 10000 km are studied. The two perturbations are due to the presence of other gravitational bodies such as Moon as a conservative perturbing forces and from the non-conservative perturbing forces such as SRP for satellite with A=5.1 m2 and m=900 kg. The position, velocity and momentum components are calculated for the perturbed equation of motion at any instant of time and thus calculate the orbital elements of each perturbation. The orbital elements for the perturbed orbit will deviate from initial elements with time. The equations of motion solved numerically using the fourth order of Runge Kutta method. The results show that the secular variation for orbital elements are true but very small.